Os municípios de pequeno porte no Brasil: aspectos socioeconômicos, fiscais e migratórios - Julia Maria Novaes Dias (2024)
The issues related to the tradeoff between centralization and decentralization of public responsibilities and resources are found at the intersection between the theoretical framework of Regional Economics and the approach of federalism. In Brazil, decentralization processes have occurred concurrently with periods of democratic transition, culminating in two emancipatory waves. Both followed the promulgation of the Constitutions in 1946 and 1988, respectively, which were processes leading to a significant increase in smaller entities in the territorial network of the country. Despite this, the national literature on these units is still incipient. Furthermore, the discussions raised by the Proposed Amendment to the Constitution - PEC 188/2019, which foresaw the extinction of municipalities with less than 5,000 inhabitants that had not met a minimum threshold of 10% of their revenue collection – called “fiscally unsustainable” – motivated as well as the investigations carried out here. Thus, Brazilian small towns were analyzed in the first paper of this Thesis, in terms of their socioeconomic characteristics, ability to offer public goods and services, and dispersion throughout the territory. They were classified according to a specific typology, which separated them into 6 distinct clusters, according to similar characteristics. Then, the capacity of self-financing of these entities was investigated in the second paper. Therefore, using a spatial PROBIT model, the factors that influence the probability of this “fiscal unsustainability” were evaluated, considering the neighborhood between municipalities and their size regimes. Beyond that, a test of structural change was carried out, to verify if there is a significative change when the municipalities surpass the size of 5,000 inhabitants. Finally, the third essay aimed to understand migratory flows – inter-city and inter-sector – of formal labor in municipalities considered here, evaluating which aspects the migration has a significant influence on, from socioeconomic and demographic points of view. Therefore, the smallest Brazilian municipalities (in terms of size, but not frequency in the territory) were placed in the focus of this Thesis. It then became possible to understand its dynamics and support different actors in the design of legislation relevant to Brazilian federalism and regional public policies.